2009
DOI: 10.1111/j.1745-3984.2009.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Logistic Regression and Contingency Table Methods for Simultaneous Detection of Uniform and Nonuniform DIF

Abstract: In this study, we investigate the logistic regression (LR), Mantel‐Haenszel (MH), and Breslow‐Day (BD) procedures for the simultaneous detection of both uniform and nonuniform differential item functioning (DIF). A simulation study was used to assess and compare the Type I error rate and power of a combined decision rule (CDR), which assesses DIF using a combination of the decisions made with BD and MH to those of LR. The results revealed that while the Type I error rate of CDR was consistently below the nomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 16 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…We used R (R Core Team, 2016) with the difR package (Magis, Beland, & Raiche, 2015). The CDR is based on a combination of the Mantel-Haenszel (MH) and Breslow-Day (BD) procedures, as MH is powerful for detecting uniform DIF and BD for detecting nonuniform DIF (Güler & Penfield, 2009). We used item purification of at least 100 iterations.…”
Section: Analysesmentioning
confidence: 99%
“…We used R (R Core Team, 2016) with the difR package (Magis, Beland, & Raiche, 2015). The CDR is based on a combination of the Mantel-Haenszel (MH) and Breslow-Day (BD) procedures, as MH is powerful for detecting uniform DIF and BD for detecting nonuniform DIF (Güler & Penfield, 2009). We used item purification of at least 100 iterations.…”
Section: Analysesmentioning
confidence: 99%
“…In addition to the results of these studies, the results of the Guler & Penfield (2009) study also show that sample sizes 300 and 1,000 can be used for DIF detection using the Mantel-Haenszel method.…”
Section: Sample Sizementioning
confidence: 79%
“…Closer guidance may be provided by simulation studies in which data sets are generated thousands of times. This approach allows the properties of different DIF detection methods to be compared with respect to their power and type I error rate (e.g., Swaminathan and Rogers, 1990 ; Narayanan and Swaminathan, 1996 ; Güler and Penfield, 2009 ; Kim and Oshima, 2013 ; Drabinová and Martinková, 2016 ). Studies like these have demonstrated that the Mantel-Haenszel method works particularly well for small sample sizes but, as expected from its formula, does not always detect nonuniform DIF ( Swaminathan and Rogers, 1990 ; Drabinová and Martinková, 2016 ).…”
Section: Resultsmentioning
confidence: 99%